2021
DOI: 10.1111/joa.13603
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of the subacromial and related shoulder bursae. An anatomical and histological study

Abstract: Shoulder bursae are essential for normal movement and are also implicated in the pathogenesis of shoulder pain and dysfunction. The subacromial bursa (SAB), within the subacromial space, is considered a primary source of shoulder pain. Several other bursae related to the subcoracoid space, including the coracobrachial (CBB), subcoracoid (SCB) and subtendinous bursa of subscapularis (SSB), are also clinically relevant. The detailed morphology and histological characteristics of these bursae are not well describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…A recent study also reported the presence of mechanoreceptors in SAB. [31] Nevertheless, mechanoreceptors were absent in our and the probability of missing the mechanoreceptor was low because it is approximately 100 times larger than the nerve fibers. [1] In this study, the preoperative VAS score measured just before the operation was 2.9 ± 1.2, which is relatively lower than that in other studies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A recent study also reported the presence of mechanoreceptors in SAB. [31] Nevertheless, mechanoreceptors were absent in our and the probability of missing the mechanoreceptor was low because it is approximately 100 times larger than the nerve fibers. [1] In this study, the preoperative VAS score measured just before the operation was 2.9 ± 1.2, which is relatively lower than that in other studies.…”
Section: Discussionmentioning
confidence: 70%
“…A recent study also reported the presence of mechanoreceptors in SAB. [ 31 ] Nevertheless, mechanoreceptors were absent in our study, and the probability of missing the mechanoreceptor was low because it is approximately 100 times larger than the nerve fibers. [ 1 ]…”
Section: Discussionmentioning
confidence: 76%
“…The SASD bursa is essential for shoulder movement and plays a key role in the subacromial gliding mechanism, which is covered by suprascapular nerve and free nerve endings ( 44 ). Several previous studies have shown that proinflammatory cytokines (IL-1β and IL-6), metalloproteases (MMPs) ( 45 ), and pain mediators (COX-2 and substance P) were associated with shoulder pain in patients with SASD bursitis.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the fact that the subacromial bursa is innervated by several nerves, such as the suprascapular nerve and the lateral pectoral nerves and contains free nerve endings [ 64 , 65 , 66 ]. Thereby, neural structures are absent in the intima and found primarily in the subintima of the bursa in close proximity to blood vessels [ 67 ]. The presence of the neuropeptide substance P was rated as the reason for shoulder pain in patients with rotator cuff disease [ 68 ].…”
Section: Bursitis and Pain: A Clear Correlationmentioning
confidence: 99%
“…The subacromial bursa is a well vascularized structure [ 13 ] with a vessel density of 1.8–3.4%, depending on whether the floor or roof of the bursa is being investigated [ 67 ]. Due to the location of the subacromial bursa, its tight fibrovascular network with high proportions of proliferating cells is also covering the tendon in the case of a tendon tear.…”
Section: Bursa As a Friend Or Foe For Rotator Cuff Repairmentioning
confidence: 99%